Continuity of traditions of students' personal development in theological educational - Alexander N. Filippov (Saratov State University, 2023)
The relevance of the research is determined by the demand for the traditions of Orthodox pedagogy. Even during the period of the official prohibition of religion and of the church in the Soviet state, Orthodox pedagogy preserved moral and spiritual values, and also influenced the approaches to upbringing in secondary schools. The purpose of the research is to identify the continuity of traditions of students' personal development in theological educational institutions. Comparing the studies of educational traditions in the early Christian school, the author highlights the characteristic features of students' personal development: education in mixed-age groups, individualized teaching, hermeneutical approach to teaching, inseparability from everyday life, connection with the family, students' personal development as the key feature of education. The study presents some examples to illustrate each of the marked characteristics. It also dwells on the self-sacrificing activity of S. A. Rachinsky, who opened a number of schools that worked in accordance with the traditions of Orthodox pedagogy. The study hypothesizes that since the time of the first Christian schools to the present days, universality and immutability of the main goal of the Orthodox education has been one of the main factors providing continuity of the traditions of students' personal development in Christian educational. This goal is connected with teaching students how to achieve the degree personal perfection available to them. The study shows that the continuity of traditions of students' personal development in theological education is also ensured by the canonical doctrine of the three-part nature of man: body, soul and spirit. The research proves that it is possible to achieve the goal of Orthodox pedagogy by means of purposeful improvement of all the components of a human. Development of the body is connected with the care of physical and mental health and is based on the rules of a godly life. Development of a person's soul involves taking care of one's personal and emotional sphere and includes such concepts as love, beauty, work, and a sense of beauty. The development of the spirit is connected with the constant training of one's will and character. The article concludes that pedagogical experience of theological educational institutions is relevant in modern conditions, since it is based on the spiritual traditions of the Russian people that are historically connected with Orthodoxy.